Efficacy of pembrolizumab and comprehensive CD274/PD-L1 profiles in patients previously treated with chemoradiation therapy as radical treatment in bladder cancer. Issue 1 (17th January 2022) - Nishimura, Kazuki; Nishio, Kyosuke; Hirosuna, Kensuke; Komura, Kazumasa; Hayashi, Takuo; Fukuokaya, Wataru; Ura, Ayako; Uchimoto, Taizo; Nakamura, Ko; Fukushima, Tatsuo; Yano, Yusuke; Takahashi, Nobushige; et al.
Abstract : Background: Chemoradiation therapy (CRT) has been increasingly reported as a possible alternative to total cystectomy (TC) for localized bladder cancer (BC). Pembrolizumab is the standard of care for platinum-refractory metastatic urothelial carcinoma, although it is unknown whether the efficacy of pembrolizumab in patients previously treated with curative CRT varies from the results of benchmark trials. Methods: We retrospectively assessed whether the survival benefit of pembrolizumab differs between patients previously treated with TC or CRT as radical treatment. A total of 212 patient records were collected for a logistic regression propensity score model. An independent dataset with next-generation sequencing (n=289) and PD-L1 Combined Positive Score (CPS: n=266) was analyzed to assess whether CRT-recurrent tumor harbors distinct CD274/PD-L1 profiles. Results: Propensity score matching was performed using putative clinical factors, from which 30 patients in each arm were identified as pair-matched groups. There was no significant difference in overall survival from the initiation of pembrolizumab (p=0.80) and objective response rate (p=0.59) between CRT and TC treatment groups. In the independent 289 BC cohort, 22 samples (7.6%) were collected as CRT-recurrent tumors. There was no significant difference in CD274 mRNA expression level between CRT-naïve and CRT-recurrent tumors. The compositions of CD274 isoforms were comparable among all isoforms detected from RNAseq between CRT-naïve (n=267) and CRT-recurrent (n=22) tumors. No actionable exonic mutation in CD274 was detected in CRT-recurrent tumors. PD-L1 CPS was positively correlated with CD274 mRNA expression level, and PD-L1 CPS was comparable between CRT-naïve and CRT-recurrent tumors. Conclusions: The efficacy of pembrolizumab for patients previously treated with CRT was similar to those treated with TC. The enhanced tumor regression by combining programmed cell death protein 1/PD-L1 inhibitor and CRT might be expected only in the concurrent administration.